MAKNA KONOTATIF METAFORA “PAPER PEOPLE” KARYA HARRY BAKER [Connotative Meaning of Metaphors in “Paper People” by Harry Baker] - Rodelio Paparang Lalenoh (TOTOBUANG, 2019)
Puisi-puisi slam Harry Baker ditulis dengan sangat memukau serta karakteristiknya dalam menyairkan puisi-slamnya yang selalu cepat, berbagi lelucon disetiap kata-kata, dan menikmati permaian kata-kata sebagai sebuah sajak. Puisinya juga dianggap mengandung begitu banyak metafora dan makna tersirat. Tujuan penelitian kualitatif ini adalah untuk mengungkapkan jenis metafora dan makna konotatif dari metafora pada puisi slam dari Harry Baker yang berjudul “Paper People” dengan menerapkan teori tipe metafora dari Stephen Ullmann dan makna konotatif Geoffrey Leech. Selain itu, penulis mengungkap bahwa terdapat 17 metafora yang dipaparkan dalam puisi slam “Paper People”. Data tersebut diklasifikasikan dalam 2 tipe metafora; 6 Metafora Antropomorfik dan 11 Metafora Konkret ke Abstrak. Makna konotatif dari puisi “Paper People” kebanyakan menyampaikan tentang inferioritas masyarakat terhadap dunia yang dewasa ini. Harry Baker’s slam poems are fascinatingly written and also his characteristic in reciting his slam poems which are always in rapid way, sharing jokes within the words and enjoy playing words as a rhyme.Otherwise,  they  also considered containing so many metaphors and their implied meaning. The intention of this qualitative research is to reveal types of metaphors and connotative meanings of metaphors in Harry Baker’s “Paper People” slam poem by applying Stephen Ullmann’s type of metaphors and Geoffrey Leech’s connotative meaning. Furthermore, the writer exposes there are 17 metaphors revealed in “Paper People” slam poem. The data are classified into 2 types of metaphors; 6 Anthropomorphic Metaphors and 11 Concrete to Abstract Metaphors. The connotative meaning of “Paper People” mostly conveys about people inferiority against present world.